Childproof your Mac. IN Features. - Marshall, Gary (Mac life)
Kids all ages love using Macs -- and that means risking them seeing, doing, and deleting things they shouldn't. This comprehensive guide shows you how to keep your beloved hardware safe--oh, and your kids too!